The relationship between religiosity level and financial satisfaction in Asian countries with multilevel modeling - Pamela Ayu Gitayani; Kismiantini (Jurnal Natural, 2026)
Subjective financial satisfaction does not always reflect objective economic conditions, as seen in several Asian countries that have strong economies but tend to report low levels of public welfare. This study differs from previous global studies in that it focuses on Asia, a region with high cultural and religious diversity. This phenomenon has prompted studies on the role of non-economic factors, such as religiosity, in shaping financial perceptions. This study aims to analyse the relationship between religiosity and sociodemographic variables on financial satisfaction in Asian countries using multilevel modeling. A multilevel approach was used because the data has hierarchical structure data (individuals nested within countries). Using a multilevel approach, this study is able to capture the influence of religiosity at both individual and country levels. This study uses secondary data from the seventh wave of the World Values Survey (WVS) (2017–2022), which includes 30,878 respondents from 20 Asian countries. The multilevel models constructed are the null model, the random intercept model, and the random slope model. Religiosity is measured through two indicators: the importance of God in life and belief in God. The results of this study indicate that the random intercept model is the best model. The importance of God, age, being female, higher education, and income positively influence financial satisfaction, while belief in God negatively influences financial satisfaction at both the individual and national levels. These findings confirm that financial satisfaction in Asian countries is not only influenced by economic factors but also by religious values and individual psychological well-being.